Dizziness profile and clinical features: a population based survey in São Paulo City, Brazil - Bittar,Roseli Saraiva Moreira (2015)
OBJECTIVE: This is a cross-sectional epidemiological survey designed to estimate the prevalence of dizziness among the adult population of the city of São Paulo, Brazil, and to describe the clinical features and level of discomfort. METHOD: This population based study was conductedin the city of São Paulo, Brazil, between April and October 2012. A total of 1,960 household interviews were completed. The following variables were assessed: gender, age, clinical characteristics of dizziness, and dizziness disability index. Chi-square test, Student's t-test,Tukey test and logistic regression were used for statistical analysis. RESULTS: The dizziness prevalence in São Paulo was 42%. Peaks of dizziness were observed in two age groups: 49% among the 46 to 55 year-old, and 44% among the elderly subjects(> 65 years-old). Vestibular vertigo was detected in 8.3% of patients, with a strong female preponderance (p < 0.001). Symptoms caused disability in 27% of the affected respondents and were more frequent among women (p < 0.001). These sought medical care more frequently (p < 0.001). The dizziness disability index was significantly higher (p = 0.0165) among subjects with a lower educational level. There was no correlation between dizziness discomfort and the type of job. CONCLUSION: The prevalence of dizziness in São Paulo, Brazil, was established at 42%. Among the symptomatic subjects, 67% reported interruption of daily activities, but only 46% of them sought medical attention.